(untitled) (Simbiótica. Revista Eletrônica, 2025)
This study investigates the role of minipublics in the context of Citizens’ Assemblies, specifically the perception of participants in the Facing Inequalities project. The adopted methodology consisted of observing deliberative sessions and conducting fifteen interviews with members of the minipublic. The results show that, from the participants’ perspective, the experiences they lived are of great importance, particularly in transforming their interest in engaging and debating public interest issues.